Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.1 Definition of the Derivative - Exercises - Page 103: 20



Work Step by Step

$k'(z)=\lim\limits_{h \to 0}\frac{k(z+h)-k(z)}{h}=\lim\limits_{h \to 0}\frac{[14(z+h)+12]-[14z+12]}{h}$ $=\lim\limits_{h \to 0}\frac{14z+14h+12-14z-12}{h}=14$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.